Nursing Remuneration Index - Suprajitno Suprajitno (Jurnal Ners, 2013)
Introduction: Nurses have some variables, which can be used as basic of the remuneration. The aim of the study was to develop nursing remuneration index in the hospital of Ngudi Waluyo Wlingi using statistics approach.Methods: Research design was descriptive, study that is divided into two levels. The fi rst level was surveying and focus group discussion and the second level was assessing the remuneration index formula by simulation. The subject for surveying was the whole nurses who have state employ status at hospital of Ngudi Waluyo Wlingi on 2011 while for the focus group discussion was the executive management and nurses. Subject for surveying were 117 nurses, while for focus group discussion was two executive management and ten nurses. The data analysis was by using AMOS software. Result: Remuneration index formed by three factors were worked place, additional job which was measured by the daily additional job and the length as observer, and kind of nursing interventions which were measured from the amount of nursing intervention in the category of simple, mild, moderate, severe, and special nursing intervention. Resulting formula of remuneration index was (0.252 x Worked place categories) + (0.226 x Additional job index) + (0.218 x Kind of nursing intervention index).Discussion: Fit assessment by using goodness of fit index was 0.827, which mean 82.7% of the remuneration index formula can be explained by factors of workplace, additional job, and kind of nursing intervention, while 17.3% was explained by other factors.